Tools to support peste des petits ruminants (PPR) control and eradication - Kotchofa, Pacem; Dione, Michel; Edward, Okoth (CGIAR, 2021)
There are an estimated 2.3 billion small ruminants (SRs) globally, with 40% in Africa (FAOSTAT 2021). For millions of smallholder herders and farmers across the continent, keeping livestock is the cornerstone of their livelihoods, contributing to household food and nutritional security and providing readily available cash income (De Haan et al. 2015). Women hold more control over SRs, compared to other livestock species such as cattle, relying on them economically but also to fulfill various socioeconomics functions, such as dowries for weddings, charity, and inheritances (Wodajo et al. 2020). Animal disease outbreaks create a significant threat to the livestock sector, negatively impacting livestock keepers. Consequently, control of major disease threats, such as peste des petits ruminants (PPR), would protect and enhance the ability of livestock keepers to benefit from their livestock. PPR is a highly contagious and viral disease, characterized by high mortality and morbidity rates, that predominantly affects sheep and goats (OIE 2021). It is endemic in most areas in Asia, the Middle East and Africa, where it was first reported and described in 1942 (Zhao et al. 2021). The control of PPR in these endemic settings presents challenges that need to be systematically addressed to ease the burden of disease on herders and farmers who are dependent on SRs for food and income. The World Organization for Animal Health (OIE) and the Food and Agriculture Organization of the United Nations (FAO) have developed a coordinated PPR Global Control and Eradication Strategy (GCES), endorsed by more than 200 countries worldwide, aiming to achieve a PPR-free world by 2030 (OIE and FAO 2015). To support this global vision, the International Livestock Research Institute (ILRI) is implementing the Epidemiology and Control of Peste des petits ruminants (ECO-PPR) research project in six countries in West and East Africa: Senegal, Burkina Faso, Mali, Kenya, Tanzania and Ethiopia.